Season of the witch - Gorn, Steve 1947- (capelight pictures, 2021)
"A neglected, unhappy suburban housewife gets mixed up in witchcraft with unexpected consequences." [imdb.com]
Original: USA 1972
Extras: Extended cut (104 Minuten) ; "When Romero met del Toro" - ein Gespräch zwischen Guilermo del Toro und George A. Romero ; "The secret life of 'Jack's Wife'" - Interview mit Darstellerin Jan White ; alternative Titelsequenzen ; Audiokommentar von Travis Crawford ; Location-Bildergalerie mit Kommentar von Lawrence DeVincentz ; Memorabilia-Bildergalerie ; Trailer
Bildformat 1.37:1 (1080p)
Keywords: Film